Long‐term child follow‐up after large obstetric randomised controlled trials for the evaluation of perinatal interventions: a systematic review of the literature. Issue 1 (19th October 2012) - Teune, MJ; van Wassenaer, AG; Malin, GL; Asztalos, E; Alfirevic, Z; Mol, BWJ; Opmeer, BC
<x xml:space="preserve">Abstract</x> Background Although the hope is that many perinatal interventions are performed with an ultimate aim to improve the long‐term health and development of the child, long‐term outcome is rarely used as a primary end‐point in perinatal randomised controlled trials (RCTs). Objective To evaluate how often and with which tools long‐term follow‐up is performed after large obstetric RCTs. Search strategy We searched the Cochrane Library for Cochrane reviews published by the Cochrane Pregnancy and Childbirth Group for reviews on interventions that aimed to improve neonatal outcome. Selection criteria Reviews on perinatal interventions that were not performed to improve the condition of the neonate were excluded. We limited our review to RCTs with more than 350 participating women. For each included study, we checked in Web of Science as to whether the researchers had reported on follow‐up in subsequent publications. Data collection and analysis Relevant information was extracted from these RCTs by two reviewers using a predefined data collection sheet. All information was analysed using SPSS 17.0 (SPSS Inc., Chicago, IL, USA). Main results We studied 212 reviews including 1837 RCTs on perinatal interventions, 249 (14%) of which included 350 participants. Only 40 of 249 RCTs (16%) followed the children after discharge from the hospital to evaluate the effect of a specific perinatal intervention. The number of RCTs with long‐term follow‐up remained stable, with 10 of 67 RCTs (15%) reporting follow‐up before 1990, 17 of 115 (15%) between 1990 and 2000, and 13 of 67 (19%) after 2000 (P = 0.68). Conclusions Only a small minority of large perinatal RCTs report the long‐term follow‐up of the child. Future obstetric RCTs should consider performing long‐term follow‐up at the start of the trial.